Development and Evaluation of E–Learning Materials with Kotobee Application in Physical Science for Grade 11 Students - Calatrava, James Andrew Ruanto (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
This study aimed to develop and evaluate e-learning materials with Kotobee Application in Physical Science as an aid for modular distance learning for Grade 11 students in selected junior and senior public high schools of the City Schools Division of Antipolo during the SY 2021-2022. Descriptive research design was used in this study. It utilized a questionnaire-checklist adopted from the Learning Resources Management and Development System of the Department of Education with some modifications to determine the acceptability of the developed learning materials in terms of content quality, instructional quality, and technical quality. Twenty science experts and 60 science teachers from different schools in Antipolo were requested to evaluate and validate the materials with respect to the aforesaid variables. The results revealed that the Science experts and teachers evaluated the developed learning materials as Very Satisfactory in terms of the said aspects. Consequently, it was found out that there was no significant difference on the evaluation of the two groups of respondents. The suggestions of the evaluators for the improvement of the material were: a) include instructional videos; b) enhance the presentations of the pictures to catch the learner’s interest; c) make sure to give a copy of key to corrections for the teacher’s reference; and d) conduct an orientation among the teachers and students for the familiarity of the application; e) target the affective aspect of the learners by including the reflection part which allows them to express their feelings towards answering the activities using the developed e-learning materials.